3 Tesla MRI brain scanning under general anaesthesia in a paediatric 3 Tesla-compatible cochlear implant recipient, first reported case: Clinical considerations and implications for future practice. (June 2020) - Zhen, Emily; Kuthubutheen, Jafri; Misso, Dylan; Rodrigues, Stephen; Thompson, Andrew
Abstract: Objectives: To demonstrate the safety and feasibility of the first reported case of a 3 Tesla MRI scan in a paediatric 3 Tesla-compatible cochlear implant recipient under general anaesthesia. Materials and methods: A three-year-old child with bilateral optic pathway glioma treated with chemotherapy, who subsequently received a right sided 3 Tesla-compatible cochlear implant for sensorineural hearing loss was examined. The CI device chosen was implanted due to its purported MRI compatibility. Following informed consent and hospital executive approval, the child underwent a 3 Tesla MRI scan to assess for growth of the optic pathway glioma. Results: A 3 Tesla MRI scan of the brain was performed under general anaesthesia. There was expected artefact due to the magnet of the receiver stimulator. There was no malfunction of the implant noted after the procedure, and no neurological or otological complications. The child had five more uneventful 3 Tesla MRI scans of the brain without complications. Conclusion: This is the first reported case of a child with a 3 Tesla-compatible cochlear implant undergoing a 3 Tesla MRI scan of the brain under general anaesthesia. Provided manufacturer guidelines are adhered to, 3 Tesla MRI scanning should not be contraindicated in paediatric cochlear implant recipients with a compatible device.